2018
DOI: 10.1097/mlr.0000000000000939
|View full text |Cite
|
Sign up to set email alerts
|

Why Effective Interventions Do Not Work for All Patients

Abstract: Failure is a common and consequential aspect of health behavior change; a deeper understanding of failure should inform chronic disease interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…While demographic attributes have been correlated with health behaviors [6], they often do not fully explain differences in intervention effectiveness [7][8][9]. Similarly, comparisons within studies suggest that baseline participant traits such as age, sex, race/ethnicity and health status are not reliable predictors of participant response [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While demographic attributes have been correlated with health behaviors [6], they often do not fully explain differences in intervention effectiveness [7][8][9]. Similarly, comparisons within studies suggest that baseline participant traits such as age, sex, race/ethnicity and health status are not reliable predictors of participant response [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Health behavior research could be improved by including additional data that informs factors influencing behavior change in intervention trials. For example, personality traits and psychological constructs such as affective response and resilience may elucidate important differences in how individuals perceive and engage with behavioral interventions that sociodemographic and clinical variables do not [12][13][14]. Evidence suggests that higher order combinations of demographic, health status, and psychosocial variables better capture the complexity of behavior change compared to any single variable type alone [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study of a community-based intervention for chronic disease management in participants with two or more diseases (i.e., diabetes, obesity, hypertension, and tobacco dependence) reported that treatment response was predicted by participants' reactions to the challenges and failures they faced during the intervention instead of their baseline characteristics; the authors concluded that behavioral interventions could be modified to help non-responders face the challenges and failures. [42] This study has limitations. First, because of the post hoc nature of the analyses the findings need to be replicated in future studies.…”
Section: Plos Onementioning
confidence: 92%
“…Third, although the total payment was scaled appropriately for this panel, it is possible that the absolute difference between individual disbursement amounts at each timepoint was not sufficiently large to influence decision-making. Finally, just as people respond differently to health-related behavioral interventions [ 35 ], it is possible that certain types of individuals were more responsive to their assigned financial incentive strategy than others [ 36 , 37 ]. For example, finding that younger and female participants were more likely to enroll overall merits further investigation.…”
Section: Discussionmentioning
confidence: 99%